Pendidikan Seksual Dalam Pencegahan Pelecehan Seksual di Sekolah Dasar - Amalina, Isna Dzulhi; Masyithoh, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to examine more deeply the importance of sexual education in overcoming sexual harassment among elementary schools and the factors that influence it. The literature study approach method is used with in-depth analysis of various literature sources and related research. The results of the analysis show that sexual education is an important foundation for children to understand reproductive health, personal boundaries, and how to protect themselves from unwanted behavior. The lack of sexual knowledge in children contributes to the increasing cases of sexual abuse. Therefore, sexual education needs to be provided both through formal education in schools and non-formal education in the family environment. Although there is still a societal stigma associated with talking about sex with children, sexual education can help develop a healthy and responsible attitude towards their bodies and prevent inappropriate sexual behavior. Thus, sexual education should be implemented appropriately and comprehensively as a preventive measure against sexual harassment among elementary school children.